Marketing in Ukraine - Kochmaruk, Maria (My University, 2012)
Several years ago Ukraine started its moving to a market-led economy. The process of transition requires fundamental economic, political and organizational restructuring of the society. It pushes the managers to change their traditional priorities from increasing production volume to identifying the appropriate target markets and developing products and services that meet the consumers’ needs. It means the strong necessity for the business units to adopt and practise effective marketing
Keywords: ефективність; ринкова економіка; маркетинг; эффективность; рыночная экономика; market economy; marketing; efficiency